2006
DOI: 10.1128/mcb.00870-06
|View full text |Cite
|
Sign up to set email alerts
|

Cotranscriptional Recruitment to the mRNA Export Receptor Mex67p Contributes to Nuclear Pore Anchoring of Activated Genes

Abstract: Transcription activation of some Saccharomyces cerevisiae genes is paralleled by their repositioning to the nuclear periphery, but the mechanism underlying gene anchoring is poorly defined. We show that the nuclear pore complex-associated Mlp1p and the shuttling mRNA export receptor Mex67p contribute to the stable association of the activated GAL10 and HSP104 genes with the nuclear periphery. However, we find no obligatory link between gene positioning and gene expression. Furthermore, gene anchoring correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
205
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(215 citation statements)
references
References 47 publications
7
205
2
Order By: Relevance
“…Taken together, these findings indicate that it is the physical presence of the SAGA complex at the GAL promoter that is required for association of the GAL genes with the NPC. Our findings are complemented by recent results suggesting that Mlp1 is an important connection between the NPC and actively transcribed genes (14), which suggests that the Mlp/SAGA link analyzed here could be a key element of locus recruitment to the NPC.…”
Section: Discussioncontrasting
confidence: 29%
See 2 more Smart Citations
“…Taken together, these findings indicate that it is the physical presence of the SAGA complex at the GAL promoter that is required for association of the GAL genes with the NPC. Our findings are complemented by recent results suggesting that Mlp1 is an important connection between the NPC and actively transcribed genes (14), which suggests that the Mlp/SAGA link analyzed here could be a key element of locus recruitment to the NPC.…”
Section: Discussioncontrasting
confidence: 29%
“…First, Mlp1 and Mlp2 interact with highly transcribed loci in genome-wide chromatin immunoprecipitation (ChIP) experiments (5). In fact, a recent study demonstrated a requirement for Mlp1 in GAL locus recruitment to the nuclear periphery (14). Second, Mlp1 has been indirectly linked to the Spt-Ada-Gcn5-acetyltransferase (SAGA) histone acetyltransferase complex through interactions between the Sac3-Thp1 mRNA export complex and the Sus1 component of SAGA (19,20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…INO1 or HXK1, like X-linked genes in male flies, show a modest but reproducible increase in expression when allowed to associate with nuclear pores [12,15,19]. On the other hand, there are other genes, notably a set of yeast ribosomal biogenesis genes, whose expression levels are lower when they are associated with nuclear pores [11,18]. This subset of promoters has a particular constellation of regulators and their localization at the nuclear pore depends on the actin-related protein Arp6 [18].…”
Section: Introductionmentioning
confidence: 99%
“…Although there is no evidence yet showing that specific pores bind specific sets of genes, recent studies implicate nuclear pores in a range of cellular processes, well beyond their function in macromolecular transport. Notably, in budding yeast and Drosophila certain highly transcribed, and in some cases stress-induced, genes are associated with nuclear pores [11][12][13][14][15][16][17][18][19]. This association not only promotes efficient export of mRNAs through coupling of transcription with export [10,11,13,14], but also helps modulate transcript levels of some loci.…”
Section: Introductionmentioning
confidence: 99%